Materials for printed boards and other interconnecting structures. Reinforced base materials clad and unclad. Brominated epoxide cellulose paper/woven E-glass reinforced laminate sheets of defined flammability (vertical burning test), copper-clad for lead-free assembly Part 2-41, (30th June 2010) - British Standards Institution,
No abstract available